2005
DOI: 10.1111/j.1365-2273.2004.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue sarcomas of the head and neck: a single‐centre experience

Abstract: The grave prognosis especially for high-grade tumours emphasizes the need for improved treatment strategies. Furthermore, conclusions from older studies concerning prognosis may be obsolete as approximately 40% of tumours previously diagnosed as sarcomas may be invalid by present day standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…In our study, most of the patients were treated with surgery + radiotherapy + chemotherapy, representing 27.8% of the cases, and surgery + radiotherapy, also with 27.8% of the cases. Other authors found lower frequencies; Penel et al 9 found 14.2% and 21.4% respectively, and Lajer et al 8 , 16.6% and 13.8%, respectively. Most studies show a large frequency of patients who were submitted to surgery only, as the studies by Bentz et al 19 , with 77% of patients, and that of Lajer et al 8 , with 52.7%.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our study, most of the patients were treated with surgery + radiotherapy + chemotherapy, representing 27.8% of the cases, and surgery + radiotherapy, also with 27.8% of the cases. Other authors found lower frequencies; Penel et al 9 found 14.2% and 21.4% respectively, and Lajer et al 8 , 16.6% and 13.8%, respectively. Most studies show a large frequency of patients who were submitted to surgery only, as the studies by Bentz et al 19 , with 77% of patients, and that of Lajer et al 8 , with 52.7%.…”
Section: Discussionmentioning
confidence: 93%
“…Gorsky and Epstein, 3 in a study on sarcomas and soft tissues, noticed that oral sarcomas represented 0.14% of all head and neck cancers, which shows how rare these tumors are. Lajer et al 8 reported from their study that oral sarcomas represented 27.7% of these head and neck tumors, and Penel et al 9 reported a 10.7% frequency.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5 However, recent reviews of pathologic soft tissue sarcoma material have changed the proportions of different sarcoma types in favor of LMS. 2,[6][7][8] Methodological advances in immunohistochemistry and molecular genetics have improved diagnostic accuracy vastly, and the majority of intraabdominal LMS have been reclassified as gastrointestinal stromal tumors.…”
mentioning
confidence: 99%
“…13 Two further cases of pharyngeal leiomyosarcoma have been described, but their exact site was unknown. 14, 15 The differential diagnosis of leiomyosarcoma includes leiomyoma, malignant melanoma, spindle cell SCC and sarcoma. Diagnosing leiomyosarcoma based on microscopy alone can be difficult, and immunohistochemical and ultrastructural investigation may be required.…”
Section: Discussionmentioning
confidence: 99%